Water splitting under visible light using aerogel prepared strontium titanate (SrTiO[subscript 3]) nanomaterials doped with ruthenium and rhodium metals - Kuo, Yenting; Klabunde, Kenneth J. (My University, 2012)
Nanostructured strontium titanate visible-light-driven photocatalysts containing rhodium and ruthenium were synthesized by a modified aerogel synthesis using ruthenium chloride and rhodium nitrate as dopants precursors, and titanium isopropoxide and strontium metal for the metal sources. The well-defined crystalline SrTiO[subscript 3] structure was confirmed by X-ray diffraction (XRD). After calcination at 500 °C, diffuse reflectance spectroscopy shows the increase of light absorption at 370 nm due to the presence of Rh[superscript 3+]; however an increase of calcination temperature to 600 °C led to a decrease in intensity, probably due to loss of surface area. An increase in rhodium doping amount also led to an increase in absorption at 370 nm; however, they higher amounts of dopant lowered photocatalytic activity. The modified aerogel synthesis allows greatly enhanced H2 production performance from an aqueous methanol solution under visible light irradiation, compared with lower surface area conventional materials. We believe this enhanced activity is due to higher surface areas while still yielding high quality nanocrystalline materials. Furthermore, the surface properties of these nanocrystalline aerogel materials are different, as exhibited by higher activities in alkaline solutions, while conventional materials (via high temperature solid-state synthesis methods) only exhibit reasonable hydrogen production in acidic solutions. Moreover, an aerogel synthesis approach gives the possibility of thin-film formation and ease of incorporation for practical solar devices.
Hydrogen generation from water/methanol under visible light using aerogel prepared strontium titanate (SrTiO[subscript 3]) nanomaterials doped with ruthenium and rhodium metals
Keywords: Condensed matter; SrTiO3; Hydrogen generation; Water splitting; Strontium titanate; Aerogel synthesis